2007
DOI: 10.2495/bio070111
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trabecular micro-architecture on vertebra biomechanics: a finite element investigation

Abstract: 700,000 vertebral fractures occur each year in the United States alone, 85% of which are associated with osteoporosis. This study presents the development of a microstructural model of an entire lumbar vertebral body to investigate the effects of osteoporotic changes in bone micro-architecture on vertebral biomechanics, specifically, the change in stiffness, stresses and load sharing capacity of the core and cortex. A finite element model of a trabecular microstructure was created using a lattice of 3D beam el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Polikeit et al [14] suggested imitating osteoporosis by adjusting only the properties of the necessary material. McDonald et al [15] examined the microstructural model of the vertebra of the lumbar region to investigate the microarchitectural changes effects of the osteoporotic trabecular bone on the vertebral instability.…”
Section: Introductionmentioning
confidence: 99%
“…Polikeit et al [14] suggested imitating osteoporosis by adjusting only the properties of the necessary material. McDonald et al [15] examined the microstructural model of the vertebra of the lumbar region to investigate the microarchitectural changes effects of the osteoporotic trabecular bone on the vertebral instability.…”
Section: Introductionmentioning
confidence: 99%